REPRESENTASI PREMANISME DALAM FILM JAGAL (Studi Semiotika Roland Barthes) - Ralvin Januar Wijaya (Universitas Bunda Mulia, 2015)
The movie titled “Jagal” (Slaughter) is interesting to be studied because it is built with signs and the field of study is very relevant for semiotic analysis. The film also tells about the history of Indonesia 60 years ago when Soeharto’s rezim execute millions people who were accused as pro-Indonesian Communist Party. The purpose of this study was to determine the thugs representation contained in the signs of communication on the film.“Jagal” raises attitudes, behavior or actions of thuggery. The act of thuggery is seen emerging among other crimes such as unlawful extortion, corruption, abuse of power, even doing by top government officials. From the analysis has been done, we can conclude the meaning of the message is the thugs emerged from someone who wants a freedom. This is a nature that emerges from within every human being. Values or meanings of thugs become familiar in people's behavior daily. Keywords: Thuggery, Semiotic, Freedom, ‘Jagal’